Restriction of growth and biofilm formation of ESKAPE pathogens by caprine gut-derived probiotic bacteria - Saini, Prerna; Ayyanna, Repally; Kumar, Rishi; Bhowmick, Sayan Kumar; Bhaskar, Vinay; Dey, Bappaditya (Frontiers in Microbiology, 2024)
The accelerated rise in antimicrobial resistance (AMR) poses a significant global health risk, necessitating the exploration of alternative strategies to combat pathogenic infections. Biofilm-related infections that are unresponsive to standard antibiotics often require the use of higher-order antimicrobials with toxic side effects and the potential to disrupt the microbiome. Probiotic therapy, with its diverse benefits and inherent safety, is emerging as a promising approach to prevent and treat various infections, and as an alternative to antibiotic therapy. In this study, we isolated novel probiotic bacteria from the gut of domestic goats (Capra hircus) and evaluated their antimicrobial and anti-biofilm activities against the 'ESKAPE' group of pathogens. We performed comprehensive microbiological, biochemical, and molecular characterizations, including analysis of the 16S-rRNA gene V1-V3 region and the 16S-23S ISR region, on twenty caprine gut-derived lactic acid bacteria (LAB). Among these, six selected Lactobacillus isolates demonstrated substantial biofilm formation under anaerobic conditions and exhibited robust cell surface hydrophobicity and autoaggregation, and epithelial cell adhesion properties highlighting their superior enteric colonization capability. Notably, these Lactobacillus isolates exhibited broad-spectrum growth inhibitory and anti-biofilm properties against 'ESKAPE' pathogens. Additionally, the Lactobacillus isolates were susceptible to antibiotics listed by the European Food Safety Authority (EFSA) within the prescribed Minimum Inhibitory Concentration limits, suggesting their safety as feed additives. The remarkable probiotic characteristics exhibited by the caprine gut-derived Lactobacillus isolates in this study strongly endorse their potential as compelling alternatives to antibiotics and direct-fed microbial (DFM) feed supplements in the livestock industry, addressing the escalating need for antibiotic-free animal products.